The act of teaching - Cruickshank, Donald R.; Bainer, Deborah L.; Metcalf, Kim K. (Boston : McGraw Hill College, 1999)
This book is about: The backdrop of teaching; The act of teaching; The effective teacher; and Practice teaching manual.
Keywords: Education; Teaching; Teaching; Lesson planning